Giftedness and gifted education: A systematic literature review - Baccassino, Francesca; Pinnelli, Stefania (Frontiers in Education, 2023)
The present study aims to discuss the state of the art inherent in pedagogical-didactic research on the education of gifted students. To this end, a systematic review of scientific texts published between 2011 and 2021 was carried out. The article is organized as follows: introduction to the topic; definition of the objectives, research questions, and methodological protocol; selection, evaluation, and synthesis of the abstract studies; discussion and evaluation of the results; conclusions. This review reveals gaps and emerging trends in gifted education research, suggesting possibilities and future perspectives.